Toughness enhancement by massive dislocation absorption at the crack front - Jiazhi Zhang; Qin Yu; Jiazhuang Tian; Shanglu Yang; Xunwei Zuo; Ying Li; Nailu Chen; Yonghua Rong; Robert O. Ritchie; Jian Lu (Proceedings of the National Academy of Sciences, 2025)
Low-cost yet high-performance structural materials have been invariantly sought for modern engineering applications. However, due to the localized stress concentration induced by a high Peierls-Nabarro stress and limited dislocation mobility, increasing material strength usually comes at the expense of ductility and toughness, resulting in a trade-off between strength–ductility/strength–toughness. Here, we report an anomalous phenomenon of dislocation absorption at the crack front, which is unlike typically observed dislocation emission at the crack tip, in a heterogeneous “plain” steel consisting of tempered lath martensite embedded with stable carbon-enriched retained austenite. The continuous absorption of dislocations emitted from the tempered martensite into the tough austenite significantly alleviates the localized stress concentration, and as such retards crack propagation in the tempered martensite matrix. This allows the plain high-carbon low-alloyed steel subjected to simple quenching–partitioning–tempering processes to achieve remarkable properties comprising a multiplication of strength and elongation over 50 GPa·% with an exceptionally high fracture toughness over 130 MPa·m 1/2 . The toughening strategy based on this mechanism provides a promising route for developing cost-effective plain steels with ultrahigh strength, ductility, and toughness that is a persistent pursuit in the steel industry.